Prognostic value of prelymphodepletion absolute lymphocyte counts in relapsed/refractory diffuse large B-cell lymphoma patients treated with chimeric antigen receptor T cells - Lu, Yanyan; Zhu, Hong; Liu, Yang; Wang, Ying; Sun, Yinxiang; Cheng, Hai; Yan, Zhiling; Cao, Jiang; Sang, Wei; Zhu, Feng; Li, Depeng; Sun, Haiying; et al. (Frontiers in Immunology, 2023)
1 Chimeric antigen receptor (CAR) T cell therapy has achieved unprecedented efficacy recently. However, the factors related to responses and durable remission are elusive. This study was to investigate the impact of pre-lymphodepletion (pre-LD) absolute lymphocyte count (ALC) on CAR T cell therapy outcomes. We conducted a retrospective study of 84 patients with relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL) who underwent CAR T cell treatment at the Affiliated Hospital of Xuzhou Medical University between March 1,2016 and December 31, 2021. The enrolled patients were divided into high group and low group according to the optimal cutoff value of pre-LD ALC. The Kaplan-Meier analyses was used to calculate survival curves. The Cox proportional hazards model was used for univariate and multivariate analysis to assess the prognostic factors. The ROC showed that the optimal cutoff value of pre-LD ALC was 1.05 x 109/L. The overall response (defined as partial response or complete response) rate was significantly higher in patients with a high pre-LD ALC (75% versus 52.08%; P=0.032). Patients with a low pre-LD ALC had significantly inferior overall survival (OS) and progression-free survival (PFS) compared with those having a high pre-LD ALC (median OS, 9.6 months versus 45.17 months [P=0.008]; median PFS, 4.07 months versus 45.17 months [P = 0.030]). Meanwhile, low pre-LD ALC is an independent risk factor for PFS and OS. The data suggested that pre-LD ALC may serve as a helpful indicator to predict the outcomes of CAR T cell therapy in patients with R/R DLBCL.